Seletividade dos herbicidas Bentazon e Nicosulfuron para Crotalaria juncea e Crotalaria spectabilis em consórcio com a cultura do milho - Nogueira, Cassio Henrique Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The species Crotalaria juncea and C. spectabilis have benefits suach as nutrients input in soil, straw production for no-tillage system, weed management and the nematicide potential. In doing so, corn intercropped with crotalaria allows better use of the agricultural year, having in the same period, economic return from grain yield and the benefits of the legume species. However, there are few informations about the the selectivity of herbicides, weed management and the interference from the legumes species in the development of corn culture, especially when in simultaneous sowing. With the objective to study the selectivity of the herbicides bentazon and nicosulfuron, isolated and in mixture, to Crotalaria juncea and C. spectabilis, when established in intercrop with corn, the weed control and the corn development in this production system. Two experiments were conducted in pots, kept in environment conditions, for selection of herbicides and dosages used in the field. In the next step, four experiments were set up in the field, two for each species, one during the late-season growing period and another one in regular growing season period. In these, the experimental design was the randomized block, with 14 treatments and four replicates. Eight treatments with herbicides were studied: bentazon (720 e 960 g i.a. ha-1), nicosulfuron (16 e 48 g i.a. ha-1) and bentazon plus nicosulfuron (720 + 16; 720 + 48; 960 + 16; 960 + 48 g i.a. ha-1). Moreover, six controls were maintained: sole corn and sole sunn hemp (with and without weeds) and corn and sunn hemp intercropped (with and without weeds). The herbicide bentazon isolated, in both dosages tested, was selective to C. juncea and C. spectabilis. Nicosulfuron in 48 g i.a. ha-1, isolated or in mixture with bentazon, promoted the best weed control. Corn affected the recoverability of C. juncea and C. spectabilis plants treated with herbicides. C. juncea intercropped without herbicides or ...

As espécies Crotalaria juncea e Crotalaria spectabilis possuem benefícios como o aporte de nutrientes no solo, a produção de palha para o plantio direto, o manejo de plantas daninhas e o potencial nematicida. Nesse sentido, o consórcio de milho com crotalária possibilita o melhor aproveitamento do ano agrícola, tendo no mesmo período o retorno econômico com a produção de grãos e os benefícios da leguminosa. No entanto, há poucas informações sobre a seletividade dos herbicidas, o manejo de plantas daninhas e a interferência da crotalária no desenvolvimento do milho, principalmente quando a semeadura das espécies é simultânea. Assim, objetivou-se estudar a seletividade dos herbicidas bentazon e nicosulfuron, isolados e em mistura, para C. juncea e C. spectabilis, quando estabelecidas em consórcio com a cultura do milho, o controle de plantas daninhas e o desenvolvimento do milho nesse sistema de produção. Dois experimentos foram desenvolvidos em vasos, mantidos em condições ambiente, para a escolha dos herbicidas e das dosagens usadas a campo. Na etapa seguinte, quatro experimentos foram instalados em campo, dois para cada espécie, um durante o período de cultivo na safrinha e o outro na safra. Nestes, o delineamento experimental foi de blocos ao acaso, com 14 tratamentos e quatro repetições. Foram estudados oito tratamentos com herbicidas: bentazon (720 e 960 g i.a. ha-1), nicosulfuron (16 e 48 g i.a. ha-1) e bentazon mais nicosulfuron (720 + 16; 720 + 48; 960 + 16; 960 + 48 g i.a. ha-1). Além disso, foram mantidas seis testemunhas: milho e crotalária solteiros (com e sem plantas daninhas) e milho e crotalária em consórcio (com e sem plantas daninhas). O herbicida bentazon isolado, nas duas dosagens testadas, foi seletivo para C. juncea e C. spectabilis. Nicosulfuron a 48 g i.a. ha-1, isolado ou em mistura com bentazon, promoveu o melhor controle das plantas daninhas. O milho afetou a capacidade de...
Keywords: Milho; Adubação verde; Intoxicação; Herbicidas; Crotalaria; Green manuring